Attorney General John Van de Kamp Keynotes Fresno County Bar Association Law Day Luncheon - Watkins, Howard::::::::: (1983)
Fresno County Bar Association President Doug Jensen, Stephen Kane, John Van de Kamp, John McGregor, Fresno County Bar Association President-Elect Rodney Worrel